4, 4, 16‐Trifluoropalmitate: Design, Synthesis, Tritiation, Radiofluorination and Preclinical PET Imaging Studies on Myocardial Fatty Acid Oxidation. (25th September 2020) - Colombano, Alessandro; Dall'Angelo, Sergio; Kingston, Lee; Grönberg, Gunnar; Correia, Claudia; Passannante, Rossana; Baz, Zuriñe; Morcillo, Miguel Ángel; Elmore, Charles S.; Llop, Jordi; Zanda, Matteo
Abstract: Fatty acid oxidation (FAO) produces most of the ATP used to sustain the cardiac contractile work, although glycolysis is a secondary source of ATP under normal physiological conditions. FAO impairment has been reported in the advanced stages of heart failure (HF) and is strongly linked to disease progression and severity. Thus, from a clinical perspective, FAO dysregulation provides prognostic value for HF progression, the assessment of which could be used to improve patient monitoring and the effectiveness of therapy. Positron emission tomography (PET) imaging represents a powerful tool for the assessment and quantification of metabolic pathways in vivo . Several FAO PET tracers have been reported in the literature, but none of them is in routine clinical use yet. Metabolically trapped tracers are particularly interesting because they undergo FAO to generate a radioactive metabolite that is subsequently trapped in the mitochondria, thus providing a quantitative means of measuring FAO in vivo . Herein, we describe the design, synthesis, tritium labelling and radiofluorination of 4, 4, 16‐trifluoro‐palmitate (1 ) as a novel potential metabolically trapped FAO tracer. Preliminary PET‐CT studies on [ 18 F]1 in rats showed rapid blood clearance, good metabolic stability – confirmed by using [ 3 H]1 in vitro – and resistance towards defluorination. However, cardiac uptake in rats was modest (0.24±0.04 % ID/g), and kinetic analysis showed reversible uptake, thus indicating that [ 18 F]1 is not irreversibly trapped. Abstract : Forever in the heart ? 4, 4, 16‐Trifluoropalmitate 1 was designed and synthesised as a novel metabolically trapped fatty acid oxidation PET imaging tracer for heart failure. The probe was radiolabelled with tritium and fluorine‐18 and was evaluated in vitro and in vivo . [ 18 F]1 showed fast clearance from the bloodstream and excellent metabolic stability; however, it was not irreversibly trapped in the heart.